Didactic and pedagogical strategies for distance learning in the context of COVID-19. Guide for teachers. - Bienvenu, KASIMU IDI (IJRDO- Journal of Educational Research, 2024)
The preparation of a courseassumes a number of educational strategies. The teacher must specify the following parameters: the content and approach to be studied; strengths and weaknesses; the needs and interests of learners; common essential learning that can be introduced; the most effective pedagogical approaches. These strategies are of crucial importance and must be taken into know-how.